Anaerobic growth of Neisseria gonorrhoeae coupled to nitrite reduction. - Knapp, J S (1984)
A total of 204 Neisseria gonorrhoeae strains, including 39 penicillinase-producing strains, representing 64 distinct auxotype and serovar classes were tested for their ability to grow anaerobically with nitrite as a terminal electron acceptor. All strains grew anaerobically with subtoxic concentrations of nitrite, and all penicillinase-producing strains produced beta-lactamase when grown anaerobically. Nitrite reductase was produced constitutively under aerobic conditions in the absence of nitrite, and cytochrome oxidase was produced constitutively under anaerobic conditions. Strains could not grow anaerobically with sulfite as a terminal electron acceptor. Strain NRL 905 grew anaerobically in broth medium containing nitrite at a rate comparable to its growth rate under aerobic conditions. The feasibility and significance of in vivo anaerobic growth of N. gonorrhoeae is discussed.